2000
DOI: 10.1359/jbmr.2000.15.11.2178
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Sequencing, and Functional Characterization of the Rat Homologue of Receptor Activator of NF-κB Ligand

Abstract: A complementary DNA (cDNA) encoding the rat homologue of receptor activator of NF-B ligand/ osteoprotegerin ligand/osteoclast differentiation factor/tumor necrosis factor (TNF)-related activationinduced cytokine (RANKL/OPGL/ODF/TRANCE) was cloned and sequenced from tibias of ovariectomized (OVX) rats. The predicted amino acid sequence of rat RANKL (rRANKL) has 84% and 96% identity to that of human and mouse RANKL, respectively, and 35% and 37% similarity to that of human and mouse TNF-related apoptosis-inducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
159
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 156 publications
(162 citation statements)
references
References 36 publications
(89 reference statements)
1
159
0
2
Order By: Relevance
“…Restriction enzymes and reverse transcriptase were purchased from Promega (Sydney, Australia), and DNA polymerase was from GeneWorks (Adelaide, Australia). GST-rRANKL 160 -318 recombinant proteins were expressed and purified in our laboratory as previously described (29). Anti-GFP rabbit polyclonal antibodies were obtained from Abcam (Sapphire Bioscience Pty.…”
Section: Methodsmentioning
confidence: 99%
“…Restriction enzymes and reverse transcriptase were purchased from Promega (Sydney, Australia), and DNA polymerase was from GeneWorks (Adelaide, Australia). GST-rRANKL 160 -318 recombinant proteins were expressed and purified in our laboratory as previously described (29). Anti-GFP rabbit polyclonal antibodies were obtained from Abcam (Sapphire Bioscience Pty.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant rat GSTrRANKL was expressed and purified as previously described. (10) TPA, LPS, recombinant TNF-␣, interleukin (IL)-1␤, and Goat anti-mouse IgG-conjugated horseradish peroxidase were obtained from Sigma (Sydney, Australia). Polyclonal antibodies to NF-B1 (p50), Rel-A (p65), c-Rel, and B-Rel, and antibodies to phospho-specific p44/42 ERK and p38 were obtained from Santa Cruz Biotechnology (Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…(8) In addition, RANKL was able to induce mature osteoclast activation in vitro (9) and osteoclast polarization and hypercalcemia in vivo. (9,10) RANKLinduced osteoclastogenesis is mediated through its receptor, RANK. The interaction of RANKL with RANK leads to the recruitment of members of the TNF receptor associated factor (TRAF) adapter proteins and the activation of the NF-〉 and c-Jun N-terminal kinase (JNK) signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have shown that RANKL is directly involved in the differentiation of macrophages into osteoclasts (Wang et al, 2003;Kukita and Kukita, 2013). RANKL is able to activate mature osteoclasts (Burgess et al, 1999), and induce osteoclast polarization and hypercalcemia (Xu et al, 2000). During stimulation with RANKL, the receptor RANK binds to signaling adaptor molecules such as tumor necrosis factor receptorassociated factor adapter proteins (Keating et al, 2007), which leads to the activation of the NFkappaB and c-Jun N-terminal kinase signaling pathways (Darnay et al, 1998).…”
Section: Introductionmentioning
confidence: 99%